The importance of financial investment using the example of the financial instrument of municipal bonds of the Municipality of Ostrów Wielkopolski - Wałęsa, Natalia (Znaczenie inwestycji finansowych na przykładzie instrumentu finansowego obligacji komunalnych w Ostrowie Wielkopolskim, 2015)
The purpose of this publication is to present the importance of financial investment using the example of the financial instrument of municipal bonds of the Municipality of Ostrów Wielkopolski. The budget support offered by the bond issue is not comparable with the possibilities of what can be achieved without issuing securities. After many years, bonds have become one of the main subjects in the capital market. Since the 1990s the issue of bonds has been growing in many municipalities including Łódź, Ostrów Wielkopolski, Kraków, Warszawa and many, many others. Unfortunately, not all of these municipalities are so eager to realise their intentions, and thus the fact is that the development is carried out in the longer term. The subject of bonds is not an easy subject, good companies operating it today have a lot of work with it and do not want to physically engage in this difficult topic. Any intentional investment and revenue in the budgets of local governments rely on financial instruments, the securities of which are municipal bonds
Ekonometria = Econometrics, 2015, Nr 1 (47), s. 78-87
Keywords: investment; financial investments; financial instruments; municipal bonds; inwestycja; inwestycja finansowa; instrument finansowy; obligacje komunalne